Resilience to Calamity in Qur'anic Perspective - Imam Aji Cahyono; Alfiyatul Azizah; Andri Nirwana AN; Fuadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to determine the resilience of calamity in the Qur'an. This research is a literature research that uses a qualitative approach. The analysis technique used is content analysis using the thematic method. The data of this research is taken from the verses of the Quran and assisted by interpretation sourced from the books of Tafsir. This study concluded that resilience to calamity in the Qur'an found three kinds: patience, repentance, and tawakkal. Patience is explained by the Qur'an in the story of Prophet Ayyub when he had a disaster in the form of illness. Repentance is defined by the Qur'an in the story of the prophet Adam when he received a disaster in the form of being lowered to the earth. Tawakkal is explained by the Qur'an in the story of the prophet Ibrahim when he was burned alive by King Namrud. These three values can be formulated and become one of the methods of spiritual resilience in the Qur'an.